Anisotropic microstructures and mechanical properties of textured Ti3AlC2/TiAl3/Al composite. Issue 22 (15th November 2022) - Wang, Zhijun; Zhang, Qiang; Ju, Boyu; Liu, Hao; Zhang, Ningbo; Zhou, Yongxiao; Shao, Puzhen; Xiu, Ziyang; Wu, Gaohui
Abstract: In the present work, a textured Ti3 AlC2 /TiAl3 /Al composite with anisotropic microstructures and properties was successfully prepared by combining multistep ball-milling, flaky powder self-assembly, spark plasma sintering (SPS), and in-situ reaction. The effects of phase constitution and crystallographic orientation on anisotropic strengthening and fracture mechanisms of the composite were discussed. The results show that the preferred orientation of Ti3 AlC2 flakes was achieved during densification with the Lotgering orientation factor of the textured top surface (TTS) of 0.58. The high surface energy of Ti3 AlC2 submicron flakes provided the driving force for the low-temperature in-situ formation of TiAl3 . The in-situ formed TiAl3 further improved the strength of the composite. The// c -axis samples achieved a high flexural strength of 565.9 MPa. The analysis of the flexural fracture surfaces shows that the fracture modes of Ti3 AlC2 flakes include basal plane cleavage, delamination, kinking, particle pull-out, and prismatic plane fracture, which in turn affects the toughness of the samples with different loading directions. Particle pull-out of the Ti3 AlC2 flakes is the primary mechanism to improve the toughness. This novel technical route provides a new idea for the design of metal matrix composites.